Experimental Investigation Of A Passive Quarter Car Suspension System - Md Ghazaly, Mariam; Siau, Ping Tee; Che Amran, Aliza; Jamaludin, Irma Wani (Asian Research Publishing Network (ARPN), 2018)
This research paper discussed the study of a two degree-of freedom quarter car model passive suspension system. An open loop characteristics experiment using system identification method was carried out to determine the transfer function of the passive suspension system. Once these steps are completed, a closed loop compensated system is designed to control the position of Platform 1; i.e. the road surface. Platform 1 will provide the road profiles of different step height for the passive quarter car suspension system. The PID controller was proven to be able to improve steady-state error by 48.6%, 31.9%, 10.9% and 21.8% for reference heights of 30cm, 32cm, 34cm and 36cm, respectively, with a slight 12% overshoot for 34cm and 36cm reference heights.